Recent advances in e-nose for potential applications in Covid-19 infection - Jay Rana; Sonal Desai (Talanta Open)
E-nose devices are designed to detect odours and flavours. The versatility and sensitivity of e-nose technology make it a valuable tool in various fields including medical diagnosis, environmental monitoring, and security and safety. The utility of e-nose is extended to detect volatile organic compounds (VOCs) in breath and other bodily fluids that are indicative of COVID-19 infection. Several studies have shown promising results in terms of accuracy and sensitivity of e-nose devices for COVID-19 detection, and this technology has the potential to be used as a non-invasive and rapid screening tool for COVID-19 in high-risk environments such as hospitals and airports. However, further research and development are needed to optimize the sensitivity and specificity of e-nose devices for COVID-19 detection, and large-scale studies are needed to confirm the accuracy and effectiveness of these devices in real-world settings. This article covers the details about the purpose, working principle of e-nose along with its applicability for COVID-19 detection.